HUBUNGAN PELAKSANAAN PEMBELAJARAN DARING DENGAN MINAT BELAJAR SISWA SMP NEGERI 4 COMAL DI MASA PANDEMI - Soeatini, Soeatini (RADIANT: Journal of Applied, Social, and Education Studies, 2021)
Pelaksanaan pembelajaran daring menjadi salah satu sarana dalam belajar mengajar di masa pandemi sekarang ini. Upaya dalam mengurangi penyebaran virus covid-19 guru di tuntut untuk bisa dalam memberikan materi mata pelajaran nya melalui media elektronik. Adapun hubungan pelaksanaan pembelajaran daring di lihat dari minat belajar siswa terutama siswa SMP Negeri 4 Comal. Penelitian ini dibuat untuk mengetahui bagaimana pelaksanaan pembelajaran dan dampak apa saja yang mempengaruhi minat belajar siswa. Bagaimana hubungan pelaksana pembelajaran daring dengan minat belajar siswa selama masa pandemic. Penelitian ini menggunakan metode kuantitatif dalam memahami hubungan antara variabel independen yakni pelaksanaan pembelajaran daring IPS dengan variable dependen yakni minat belajar siswa. Â  The implementation of online learning is one of the means of teaching and learning in the current pandemic. The teachers are required to be able to provide subject matter through electronic media and this is the efforts to reduce the spread of the Covid-19 virus. The relationship between the implementation of online learning is seen from the students' interest in learning, especially students of SMP Negeri 4 Comal. This research was made to determine how the implementation of learning and what impacts affect student interest in learning. How do online learning implementers relate to student learning interest during a pandemic. This study uses quantitative methods in understanding the relationship between the independent variables, namely the implementation of social studies online learning with the dependent variable, namely students' interest in learning.